Ultrasound characterization of middle ear effusion - Seth, Rahul; Discolo, Christopher M.; Palczewska, Grazyna M.; Lewandowski, Jan J.; Krakovitz, Paul R. (American journal of otolaryngology, 2013)
To further enhance and assess the ability to characterize middle ear effusion (MEE) using non-invasive ultrasound technology. This is a prospective unblinded comparison study. Fifty-six children between the ages of 6months and 17years scheduled to undergo bilateral myringotomy with pressure equalization tube placement were enrolled. With the child anesthetized, the probe was placed into the external ear canal after sterile water was inserted. Ultrasound recordings of middle ear contents were analyzed by computer algorithm. Middle ear fluid was collected during myringotomy and analyzed for bacterial culture and viscosity. Ultrasound waveforms yielded a computer algorithm interpretation of middle ear contents in 66% of ears tested. When a result was obtained, the sensitivity and specificity for successfully characterizing middle ear fluid content as either void of fluid, thick fluid (mucoid), or thin fluid (serous or purulent) were at least 94%. Mucoid effusions had higher measured viscosity values (P=.002). Viscosity measures were compared to culture result, and those with low viscosity (thin consistency) had a higher likelihood of having a positive culture (P=.048). The device sensitivity and specificity for fluid detection were 94% or greater among interpretable waveforms (66% of those tested). Although this technology provides important information of the middle ear effusion presence and characteristic, further technological improvements are needed.